An Electrochemical ATP Biosensor with Enzymes Entrapped within a PEDOT Film. Issue 2 (16th October 2020) - Peteu, Serban F.; Russell, Skye A.; Galligan, James J.; Swain, Greg M.
Abstract: This paper reports on the electrochemical behavior of an ATP biosensor that utilizes glucose oxidase (GOx) and hexokinase (Hex) immobilized within the electroactive polymer, polyethylenedioxythiophene (PEDOT). This biosensor design detects ATP indirectly at 0.85 V vs. Ag/AgCl based on the oxidation current for enzymatically generated H2 O2, and at −0.20 V; a potential at which improved analyte selectivity is achieved. The detection figures of merit at both detection potentials are a response time of 15±1 s, an experimental detection limit of 10.0±0.2 μmol L −1 (S/N=3), and a sensitivity in the range of 100–500 mA M −1 cm −2 . Abstract :